Retail Investor Protection Through Information Disclosure in the Domestic Capital Market - Santoso, Bambang; Negara, Dharma Setiawan; Putra, Arif Rachman (Metromedia, 2025)
This study examines the protection of retail investors in the capital market using a normative legal approach, focusing on the authority of the Financial Services Authority (OJK), the disclosure obligations of issuers, and the available law enforcement mechanisms. The analysis was conducted through a review of primary legal materials in the form of capital market laws and regulations and secondary legal materials. The results of the study show that the legal framework has provided a broad set of tools to reduce information asymmetry and provide room for retail investors to recover their losses. The OJK has a regulatory and supervisory mandate that includes setting disclosure standards, monitoring compliance, conducting special examinations, and applying graduated sanctions. At the regulatory level, issuers' obligations are linked to accounting standards, audits, and the supervision of supporting professions, so that the quality of information can be tested through several layers of supervision. However, the effectiveness of protection is still influenced by the limited financial literacy and legal capacity of retail investors, the cost and time barriers to litigation, and institutional challenges in supervising an increasingly digitalised market. Therefore, it is necessary to strengthen the quality of information disclosure that is reader-friendly for small investors, increase the transparency of law enforcement by authorities, and develop more accessible dispute resolution mechanisms, including support for retail investor organisations as dialogue partners in the formulation of capital market policies oriented towards investor protection.